Writing readiness and children with Down Syndrome in an Irish context. Issue 3 (July 2016) - Patton, Sandra; Hutton, Eve
Abstract : There is a dearth of studies investigating writing readiness in children with Down Syndrome (DS) and limited information on appropriate interventions. This article reports on a study conducted in the Republic of Ireland. An uncontrolled pretest‐posttest design was implemented using writing readiness measures specifically adapted/developed from the literature to collect data on the writing readiness skills of 28 school‐aged children with DS attending mainstream schools in the Republic of Ireland. Teacher/parent perspectives were also gathered during focus groups. The children presented with complex needs in relation to posture, pencil grasp, copying basic shapes, name/letter copying. Teacher and parent reports highlighted the need for collaborative intervention with occupational therapy. Findings from the study support the need for targeted early collaborative syndrome‐specific intervention to support the development of writing readiness in children with DS as an important part of school readiness. Intervention should include adopting a broader emergent literacy approach, teacher education regarding writing readiness and parental involvement in intervention.